Digital literacy research trends and collaborations in EFL classrooms: A bibliometric analysis of language learning transformation - Farhaini Uswah; Bambang Widi Pratolo; Ani Susanti (Englisia: Journal of Language, Education, and Humanities, 2026)
The rapid advancement of digital literacy has catalyzed the transformation of technology-based English as a Foreign Language (EFL) instruction. Nevertheless, comprehensive mappings of research trends, thematic focal points, and current scholarly collaborations remain insufficiently integrated. Moreover, the scarcity of empirical research has often compelled teachers and learners to develop technological innovations independently. This study seeks to delineate the trajectory of digital literacy research within technology-based EFL learning, focusing on prevailing themes, patterns of research collaboration, and projected directions. Employing a qualitative bibliometric approach, this study analyzes 55 documents indexed in Scopus over the past five years, with data visualization conducted using RStudio. The findings reveal a pronounced emphasis on cognitive enhancement, the predominance of Mobile-Assisted Language Learning (MALL) and self-directed learning as the most highly cited concepts, the emergence of two principal thematic clusters—digital literacy with learning autonomy, and digital literacy with Computer-Assisted Language Learning (CALL)—as well as a robust regional collaboration network within Southeast Asia. These results confirm that digital literacy, EFL, and CALL constitute the core thematic foundations of technology-mediated language learning. Concurrently, the findings underscore the necessity for further research employing mixed-methods designs to develop a more holistic understanding of how to foster sustainable innovation in EFL learning grounded in digital literacy.